Waste siege : the life of infrastructure in Palestine - Stamatopoulou-Robbins, Sophia (Stanford studies in Middle Eastern and Islamic societies and cultures., 2020)
"In 1995, with the establishment of the Palestinian Authority, Israel transferred responsibility for waste management in the West Bank to the nascent Palestinian government. While electricity, water, roads, and telecommunications remained largely controlled by Israel building new waste infrastructures and controlling the movements and effects of Palestinians' wastes became central to efforts to demonstrate the Authority's ability to be state-like. Waste Siege asks what is made possible, and what other ways of being are foreclosed, in the rubble, debris, and infrastructural fallout of decades of struggle to live a livable life among waste. Tracing Palestinians' own experiences of wastes over the past decade highlights the significance of the presence of multiple governing authorities in the West Bank-including municipalities, the Palestinian Authority, international aid organizations, NGOs, and political groups, as well as Israeli control-shows how all of these actors rule Palestinian lives by waste siege"--